2020
DOI: 10.1002/aocs.12404
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Quercetin Palmitate Esters and Evaluation of their Physico‐Chemical Properties and Stability

Abstract: Quercetin was acylated with palmitic acid, catalyzed by either Candida antarctica lipase B (CAL‐B) or Pseudomonas cepacia lipase C (PCL‐C) to produce quercetin palmitate esters. The effects of various operating factors including incubation temperature, reaction duration, and molar ratio of substrates on the bioconversion yield, initial rate of reaction, and regioselectivity of the reactions were investigated. Three new esters were identified: quercetin 4′‐palmitate (C31H40O8, 540 g mol−1), quercetin 3′,4′‐dipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…On the other hand, the solubility of the C12 and C16 derivatives was 3 times lower than that of aglycone. A similar increase in lipophilicity and the partition coefficient (log P ) upon acylation has also been reported for other flavonoids. , …”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…On the other hand, the solubility of the C12 and C16 derivatives was 3 times lower than that of aglycone. A similar increase in lipophilicity and the partition coefficient (log P ) upon acylation has also been reported for other flavonoids. , …”
Section: Resultssupporting
confidence: 78%
“…A similar increase in lipophilicity and the partition coefficient (log P) upon acylation has also been reported for other flavonoids. 49,50 Regarding the stability, we observed that the synthesized acyl-glucosides exhibit significant stability over several days under neutral and mildly acidic pH conditions (Figure S12). However, at pH 8.0, we noted a gradual hydrolysis of the ester bond, resulting in approximately 25% conversion to the respective monoglucoside over an 8-day period.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The active ingredient, quercetin, has low solubility, absorption and bioavailability despite having many benefits as a medicinal and supplement ingredient. Thus, it is necessary to create a delivery system that can improve its properties-one of which is niosome preparations (Lesjak et al, 2018;Saik et al, 2020;Wang et al, 2016). Additionally, niosomes also have advantages in transdermal drug delivery such as sustained drug release, improved penetration and higher skin retention (Kumar & Goindi, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…However, the low solubility, absorption and bioavailability of quercetin limit its practical use as a drug or supplement, and thus a wealth of research has been conducted to address these issues (Praven, 2014;Sadeghi-Ghadi, 2020). Notably, various drug delivery systems have been developed to increase the water solubility of quercetin (Lesjak et al, 2018;Saik et al, 2020;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to the solubility–diffusion model of the Meyer–Overton rule, for the molecules predominately rely on passive transport to penetrate the cellular membrane, such as flavonol aglycones, their membrane permeability can be well predicted from (and are positively correlated with) the oil–water partition coefficient, namely, increased lipid solubility promotes permeation of such compounds through lipid bilayer . For example, Saik et al enzymatically acylated quercetin with palmitic acid; the product quercetin-4′- O -monopalmitate/3′,4′- O -dipalmitate/7,3′,4′-tripalmitate showed enhanced lipophilicity and stability in the simulated gastrointestinal environment compared to quercetin. In the study of Hu et al, the permeability coefficient for apical-to-basolateral (AP-BL) transport of quercetin tetraester [3′,4′,3,7- O -(2-ethoxy-2-oxo)­ethyl quercetin ester] in Caco-2 cells (5.23 × 10 –6 cm/s) was nearly double than that of quercetin (2.82 × 10 –6 cm/s).…”
Section: Introductionmentioning
confidence: 99%